2021
DOI: 10.1155/2021/5513690
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Profiles Are Affected in Serum of Patients with Acute Rejection of Kidney Allograft

Abstract: Kidney allograft transplantation improved the prognosis and quality of life of patients with end-stage renal diseases but the occurrence of acute rejection represents a limitation of the final outcome. Noninvasive biomarkers are needed as well as further advancements in the understanding of immune mechanisms of reaction to the allograft. Our study of 138 patients focused on one-year monitoring of serum concentrations of 12 chemokines regulating the recruitment of different immune cells into transplanted allogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Several studies have demonstrated that urinary CXCL10 expression is significantly elevated during AKI [48]. The pretransplant elevation of serum CXCL10 concentration in patients with acute rejection shows an association with the risk of graft failure [48,49]. Urinary CXCL10 levels increase in patients experiencing acute rejection [50] and in pediatric patients with declining renal allograft function [51].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that urinary CXCL10 expression is significantly elevated during AKI [48]. The pretransplant elevation of serum CXCL10 concentration in patients with acute rejection shows an association with the risk of graft failure [48,49]. Urinary CXCL10 levels increase in patients experiencing acute rejection [50] and in pediatric patients with declining renal allograft function [51].…”
Section: Discussionmentioning
confidence: 99%
“…This process is facilitated by the upregulation of endothelial adhesion molecules and the release of chemokines from parenchymal cells. Krupicekova et al [ 26 ] found that 44 patients with acute allograft rejection had higher serum levels of chemokines (i.e., CXCL1, CXCL5, CXCL6, CCL2, CCL21, and particularly CXCL10; and CX3CL1 before transplantation), which suggested their higher inflammatory state. Samples collected on the day of kidney biopsy displayed positive results for acute rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The HEALTH signature features the chemokines CXCL1, CXCL8 (IL-8), CCL4 (MIP-1β), and lymphotoxin alpha (TNFB). The association with renal inflammation is surprising ( 47 49 ), suggesting that the metabolic health signature (MB up, Figure 3 ) cannot be interpreted as the homeostatic state of the allograft. We hypothesize that the INJURY signature represents one distinct injury pattern that is independent of the serum regulation of these chemokines.…”
Section: Discussionmentioning
confidence: 99%